2003
DOI: 10.1017/s0021859603003435
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the dynamic growth and development traits of peanut lines

Abstract: Physiological traits responsible for differences in yield performance among pre-released genotypes are normally not known. The objective of the present study was to evaluate seasonal variations in dynamic growth and development traits between 12 large-seeded Virginia-type and 14 small-seeded Spanish-type advanced breeding lines of peanut (Arachis hypogaea L.). The experiment was conducted in 1999 and 2000 at Khon Kaen University in Northeast Thailand for three planting dates, representing the early-rainy seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…Overall, the pattern and magnitude of LAI measurements across the season in this study were typical for other peanut cultivars (Banterng et al, 2003;Kiniry et al, 2005), but some studies have documented a more parabolic pattern for LAI development (Kar and Kumar, 2007) as well. Patterns of growth in the current study indicated that late-maturing cultivars had higher late-season growth than mid-maturing cultivars.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Overall, the pattern and magnitude of LAI measurements across the season in this study were typical for other peanut cultivars (Banterng et al, 2003;Kiniry et al, 2005), but some studies have documented a more parabolic pattern for LAI development (Kar and Kumar, 2007) as well. Patterns of growth in the current study indicated that late-maturing cultivars had higher late-season growth than mid-maturing cultivars.…”
Section: Discussionsupporting
confidence: 54%
“…Although an early study indicated that peanut yield was determined more by genetic pedigree than growth habit (Norden and Lipscomb, 1974) more recent studies show a strong link between growth and reproduction for other legumes (Krishnamurthy et al, 1999) and other peanut culitvars (Bennett et al, 1993;Banterng et al, 2003). In the current study, traits relating to canopy development (and thus assimilation capacity) as well as mid-season reproductive potential appeared to be causally linked to final reproductive output in the late season.…”
contrasting
confidence: 46%
See 3 more Smart Citations